CURRENT SCENARIO OF THE INSTITUTIONALIZATION OF THE SPECIAL COFFEE MARKET IN BRAZIL: A COMPARISON BETWEEN 1990 AND 2016 - de Carvalho, Josue Pires; Arévalo, Jorge Luis Sánchez; Passador, João Luiz (Revista de Negócios, 2018)
This study analyzes the importance of isomorphic relations in the process of institutionalization of the special coffee market in Brazil. To accomplish the objective, interviews were conducted with the various agents tied to the field. Three Brazilian regions were chosen because they are the most representative and convenient for the study, considering their high institutional development; two (Northwest of Minas and Alta Mogiana) already have Geographical Indications (GI) and the third one (Matas de Minas) is in the process of adoption. The results show the importance of the State as between promoter and inducer in relation to the adoption of GIs. In addition, it is evident the importance of the commitment of agents - producer and buyer - who are proactively engaged in entrepreneurial actions, in order to adapt to the new practices and trends of the special coffee market, where quality consumption is privileged.